Collagen peptide supplementation before bedtime reduces sleep fragmentation and improves cognitive function in physically active males with sleep complaints. - Thomas, Craig; Kingshott, Ruth N.; Allott, Kirsty M.; Tang, Jonathan C. Y.; Dunn, Rachel; Fraser, William D.; Thorley, Josh; Virgilio, Nicolina; Prawitt, Janne; Hogervorst, Eef; Škarabot, Jakob; Clifford, Tom (European Journal of Nutrition, 2024)
Purpose: The primary aim of this study was to examine whether a glycine-rich collagen peptides (CP) supplement could enhance sleep quality in physically active men with self-reported sleep complaints. Methods: In a randomized, crossover design, 13 athletic males (age: 24 ± 4 years; training volume; 7 ± 3 h·wk1) with sleep complaints (Athens Insomnia Scale, 9 ± 2) consumed CP (15 g·day1) or a placebo control (CON) 1 h before bedtime for 7 nights. Sleep quality was measured with subjective sleep diaries and actigraphy for 7 nights; polysomnographic sleep and core temperature were recorded on night 7. Cognition, inflammation, and endocrine function were measured on night 7 and the following morning. Subjective sleepiness and fatigue were measured on all 7 nights. The intervention trials were separated by ≥ 7 days and preceded by a 7-night familiarisation trial. Results: Polysomnography showed less awakenings with CP than CON (21.3 ± 9.7 vs. 29.3 ± 13.8 counts, respectively; P = 0.028). The 7-day average for subjective awakenings were less with CP vs. CON (1.3 ± 1.5 vs. 1.9 ± 0.6 counts, respectively; P = 0.023). The proportion of correct responses on the baseline Stroop cognitive test were higher with CP than CON (1.00 ± 0.00 vs. 0.97 ± 0.05 AU, respectively; P = 0.009) the morning after night 7. There were no trial differences in core temperature, endocrine function, inflammation, subjective sleepiness, fatigue and sleep quality, or other measures of cognitive function or sleep (P > 0.05). Conclusion: CP supplementation did not influence sleep quantity, latency, or efficiency, but reduced awakenings and improved cognitive function in physically active males with sleep complaints.